Chronically Ill Households, Food Security, and Coping Strategies in Rural Zimbabwe - Senefeld, Shannon; Polsky, Ken (International Food Policy Research Institute, 2006)
The more we learn about the interaction between HIV/AIDS and livelihoods, the more complex the picture seems to become. Although we must avoid paralysis in the face of such complexity, we must also be humble about our perceptions. We must look closely at the local context and the diverse external factors in addition to HIV and AIDS that constrain households and livelihoods at any given time. Limited information exists on the actual impacts of HIV/AIDS on coping strategies and how to operationalize programming to respond to any impacts that do exist. This research aimed to identify how HIV/AIDS impacts coping strategies in rural Zimbabwe and how these impacts could be factored into the design of humanitarian programs. To further our understanding of the relationships between HIV/AIDS and livelihood security in rural Zimbabwe, we isolated and analyzed a number of different variables.